Dynamic pricing models and negotiating agents: Developments in management accounting - Edgard B. Cornacchione; Luciane Reginato; Joshua Onome Imoniana; Marcelo Souza (Administrative Sciences, 2023)
Linking decision systems, negotiating agents, management accounting, and computational accounting, this paper aims at exploring dynamic pricing strategies of a synthetic business-to-consumer online operation and a comparative analysis of evolving strategy-specific pricing optimization. Five price models based on market, utility, or demand information (three single and two combined), merging online and offline data, are explored over a seven-day period and with twenty selected products. A total of 17,529 website visits and 538 agent negotiations are studied (94,607 main data points) using a Python solution, with model simulation parameters and assumptions described. Findings show the combined market-utility-demand performance of dynamic pricing to be superior as an input to the negotiating agent. Contributions are threefold, pointing to (a) management accounting practice and research (dynamic pricing), (b) science and research strategy (method), and (c) accounting education (skill set).
Keywords: 350; business-to-consumer; buyer behavior; computational accounting approach; data analytics; dynamic pricing; management accounting; negotiating agents; revenue management